A world without rinderpest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Rinderpest, the most devastating of cattle diseases, has been restricted to just a few pockets of infection in Ethiopia, Kenya and Sudan and could soon be totally eradicated from Africa, thus saving African nations and donors millions of dollars a...